Vitamin D improves sunburns by increasing autophagy in M2 macrophages - Das, Lopa M. (Autophagy, 2019)
Cutaneous inflammation from UV radiation exposure causes epidermal damage, cellular infiltration, and secretion of pro-inflammatory mediators that exacerbate tissue destruction. Recovery is mediated chiefly by anti-inflammatory M2 macrophages that suppress inflammation and augment epidermal regeneration. Vitamin D enables anti-inflammation to promote tissue repair in response to injury. Since vitamin D enhances cellular macroautophagy/autophagy, we investigated the role of autophagy in vitamin D protection of UV-mediated sunburn and inflammation. Using a UV-mediated acute skin injury mouse model, we demonstrate that a single dose of vitamin D resolves injury with sustained inhibition of inflammatory cytokines associated with enhanced autophagy in myeloid anti-inflammatory M2 macs. Increased MAP1LC3B/LC3 expression corroborated with complete autolysosome formation detected by electron microscopy and correlated with degradation of SQSTM1/p62 in the skin following vitamin D treatment. Specifically, pharmacological inhibition of autophagy increased UV-induced apoptosis, suppressed M2 macs recruitment, and prevented vitamin D downregulation of Tnf and Mmp9 in the skin. Furthermore, selective deletion of autophagy in myeloid cells of atg7 cKO mice abrogated vitamin D-mediated protection and recapitulated UV-induced inflammation. Mechanistically, vitamin D signaling activated M2-autophagy regulators Klf4, Pparg, and Arg1. Lastly, analysis of UV-exposed human skin biopsies detected a similar increase in macrophage autophagy following vitamin D intervention, identifying an essential role for autophagy in vitamin D-mediated protection of skin from UV damage. Abbreviations: ARG1: arginase 1; ATG7 cKO: autophagy related 7 conditional knockout; HPF: high powered field; KLF4: Kruppel like factor 4; MAP1LC3B/LC3: microtubule-associated protein 1 light chain 3 beta; macs: macrophage; 3-MA: 3-methyladenine; MMP9: matrix metallopeptidase 9; NOS2: nitric oxide synthase 2, inducible; PPARG: peroxisome proliferator activated receptor gamma; SQSTM1/p62: sequestosome 1; TNF: tumor necrosis factor; UV: ultraviolet; VD: vitamin D, 25-hydroxy vitamin D(3); 1,25-VD: 1, 25-dihydroxy vitamin D(3)